2008
DOI: 10.1021/nn800400u
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Preformed Cobalt-Doped Platinum Nanocatalysts For Ultraselective Hydrogenation

Abstract: Bimetallic heterostructures are used as industrial catalysts for many important transformations. However, conventional catalysts are primarily prepared in cost-effective manners without much appreciation in metal size control and metal-metal interaction. By employing recent nanotechnology, Pt nanocrystals with tailored sizes can be decorated with Co atoms in a controlled manner in colloid solution as preformed nanocatalysts before they are applied on support materials. Thus, we show that the terminal CO hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
122
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(136 citation statements)
references
References 24 publications
5
122
0
Order By: Relevance
“…It was observed that additional Co atoms decorating the surface of Pt nanocrystals lead to increased selectivity of hydrogenation reactions. 57 …”
Section: Disordered Fe-pt Nanoparticlesmentioning
confidence: 99%
“…It was observed that additional Co atoms decorating the surface of Pt nanocrystals lead to increased selectivity of hydrogenation reactions. 57 …”
Section: Disordered Fe-pt Nanoparticlesmentioning
confidence: 99%
“…When cobalt decorates the surface of platinum nanoparticles, the composite nanoparticles can be used as ultra-selective hydrogenation catalysts for the production of unsaturated alcohols [21]. Pt-Co or Pt-Fe nanoparticles deposited on carbon supports (Pt-Co/C or Pt-Fe/C) were used as methanol-tolerant oxygen reduction electrocatalysts [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] Platinum is a promising catalyst for this challenging reaction, in which hydrogenation of the C=C bond is both kinetically and thermodynamically more favourable than the C=O function, 20 and hence the influence of the physicochemical properties of platinum nanoparticles is a topic of much intensive recent investigation in batch reactors. Particle size effects upon CinnOH selectivity have proved controversial, with oleic acid/oleylamine stabilised mono-and bimetallic colloidal Pt nanoparticles reported to exhibit a strong size dependence of CinnOH selectivity, with low coordination sites favoring C=C hydrogenation, 21,22 whereas Zhu and Zaera reported that CinnOH selectivity was insensitive to the size of silica supported Pt nanoparticles albeit over a narrow size range. 23 Guo et al have shown that confinement of Pt nanoclusters within the cavity of metal-organic frameworks also promotes CinnOH selectivity; with steric constraints on CinnALD believed to hinder C=C planar adsorption with consequent preferential C=O activation.…”
mentioning
confidence: 99%